Aglomerasi Industri Pengolahan Di Wilayah Kabupaten Jember Tahun 2011-2015 - Yuli Wulandari; Endah Kurnia Lestari; I Wayan Subagiarta (UPT Penerbitan Universitas Jember, 2019)
The concentration of economic activity in the world, has become an interesting phenomenon to be analyzed. The existence of a product program in a region will lead to cultural growth in a sustainable state on two kinds of economic externalities namely, localization economy and urbanization economy commonly called economic agglomeration. The agglomeration economy arises because an industry will choose the place where it will guarantee the production process for a long time. The purpose of this study is to identify the magnitude of agglomeration strength in the sub-sector of the food, beverage and tobacco industries in Jember district. The population of this research is the sub-district in Jember Regency. The method of acculating data used are doumentation comes from BPS and Disperindag Jember District. The analysis used is Ellison Glaeser index. Based on the results of the analysis, it is known that all four sub-districts (Wuluhan, Ambulu, Rambipuji and Kalisat) have moderate concentration levels, where concentrated areas occur because of the agglomeration power (agglomeration effect) in each region due to the influence of externalities in the form of natural advantages and knowledge spillover. Keywords: Agglomeration, Eksternality, Cluster, Specialization.